ANALISIS MODEL PEMBELAJARAN KEWIRAUSAHAAN BERBASIS MIND MAPPING Di SMK NEGERI 4 MAKASSAR - Agus Syam (Tasharruf: Journal Economics and Business of Islam, 2018)
This study was conducted to answer the problem "Is Entrepreneurship Learning Outcomes on Attitude and Behavior Basic Competence can Entrepreneurial Enhanced Through Cooperative Learning Mind Mapping" . Thus, this research aims to improve learning outcomes in basic competency entrepreneurial attitude entrepreneur behavior after the application of the Mind Mapping . To that end , the results of this study would be useful: (1) theoretical, (a) for the academic/educational institutions, the subject of the information in the development of science, particularly in improving learning outcomes Entrepreneurship, (b) for researchers, as experience is extremely valuable in conduct scientific studies, and further research is as a comparison as well as reference materials for relevant research, (2) practical, (a) for the teacher, can assist teachers in improving student learning outcomes in the classroom through the implementation model of Mind Mapping, (b) for students, more motivated and interested in participating in the process of entrepreneurial learning in order to improve student learning outcomes in learning, and (c) for schools, provide information and input to the script on the use of models Cooperative learning activities.Study is a classroom action research is descriptive, where the setting and subject of research conducted in 10 marketing class 3 which were 30 students at SMK Negeri 4 Makassar. This study conducted two cycles consisting of four activities: planning (planning), execution (action), observation (observation) and reflection. Data collection techniques used are observation, testing and documentation. With the increasing number of products to organize learning outcomes on average test scores in the first cycle of the category of very less ie 51.42 percent increase to 88.57 percent which is well on the second cycle.The results showed that the application of cooperative learning model to improve learning outcomes Script grade students of SMK Negeri 4 Makassar class 10 Marketing 3. As a follow-up suggested the need for the application of the developed models Mind Mapping learning as an alternative to increase motivation and learning outcomes in order to improve the quality of the learning process in schools, Cooperative learning Mind Mapping can be often applied not only on the competence of managing the product but other subjects as well, in case the student can focus more attention to learning when the learning process takes place, sought as early as possible to overcome the difficulties experienced, both by students and teachers in the learning process. Keywords: Mind Mapping Based Entrepreneurship Learning